Examining cultural impacts on consumers’ environmental CSR outcomes - Bhalla, Nandini; Overton, Holly K (Corporate communications, 2019)
Purpose The purpose of this paper is to examine the impact of cultural factors on environmental CSR attitudes and purchase intentions among publics in a developed (USA) country and a developing (India) country. Design/methodology/approach Using a 2 (location of the company: India vs USA) × 2 (location of the CSR activity: India vs USA) between-subjects experimental design, the study examines individuals’ attitudes and behavioral intentions toward a company’s environmental CSR activities in each respective country. Findings Two structural equation models were created for US publics and Indian publics. Results indicated that cultural factors, specifically the uncertainty avoidance dimension, play an important role among both Indian and US residents’ attitudes toward a company’s environmental CSR efforts and their intention to purchase its products/services. Among Indians, the power distance dimension acted as a mediating factor. Originality/value This study is novel in its examination of the impact of cultural factors among residents in India and the USA. This information can be utilized by multinational companies to implement effective CSR activities and enhancing their global CSR communication efforts.